Characterizing dose response relationships: Chronic gamma radiation in Lemna minor induces oxidative stress and altered polyploidy level. (December 2015) - Van Hoeck, Arne; Horemans, Nele; Van Hees, May; Nauts, Robin; Knapen, Dries; Vandenhove, Hildegarde; Blust, Ronny
Abstract: The biological effects and interactions of different radiation types in plants are still far from understood. Among different radiation types, external gamma radiation treatments have been mostly studied to assess the biological impact of radiation toxicity in organisms. Upon exposure of plants to gamma radiation, ionisation events can cause, either directly or indirectly, severe biological damage to DNA and other biomolecules. However, the biological responses and oxidative stress related mechanisms under chronic radiation conditions are poorly understood in plant systems. In the following study, it was questioned if the Lemna minor growth inhibition test is a suitable approach to also assess the radiotoxicity of this freshwater plant. Therefore, L. minor plants were continuously exposed for seven days to 12 different dose rate levels covering almost six orders of magnitude starting from 80 μGy h −1 up to 1.5 Gy h −1 . Subsequently, growth, antioxidative defence system and genomic responses of L. minor plants were evaluated. Although L. minor plants could survive the exposure treatment at environmental relevant exposure conditions, higher dose rate levels induced dose dependent growth inhibitions starting from approximately 27 mGy h −1 . A ten-percentage growth inhibition of frond area Effective Dose Rate (EDR10 ) was estimated at 95 ± 7 mGy h −1, followed by 153 ± 13 mGy h −1 and 169 ± 12 mGy h −1 on fresh weight and frond number, respectively. Up to a dose rate of approximately 5 mGy h −1, antioxidative enzymes and metabolites remained unaffected in plants. A significant change in catalase enzyme activity was found at 27 mGy h −1 which was accompanied with significant increases of other antioxidative enzyme activities and shifts in ascorbate and glutathione content at higher dose rate levels, indicating an increase in oxidative stress in plants. Recent plant research hypothesized that environmental genotoxic stress conditions can induce endoreduplication events. Here an increase in ploidy level was observed at the highest tested dose rate. In conclusion, the results revealed that in plants several mechanisms and pathways interplay to cope with radiation induced stress. Highlights: L. minor growth inhibition test is not appropriate to analyse environmental exposure situations. L. minor plants showed dose dependent growth inhibition at increasing levels of external gamma radiation. EDR10 values on growth related endpoints obtained in the present study ranged from 95 to 154 mGy h −1 . Catalase showed the most sensitive response from the antioxidative enzymes tested. Ploidy level was increased at the highest tested dose rate.